TRANSGENIC NICOTIANA TABACUM PLANTS CARRING RNAi CONSTRUCT RESISTANT TO TWO MOSAIC VIRUSES - Vân, Phạm Thị; Hà, Chu Hoàng; Bình, Lê Trần (Vietnam Journal of Biotechnology, 2011)
Tobacco  mosaic  virus  (TMV)  and  cucumber  mosaic  virus  (CMV)  is  one  of  the  most  important  viral pathogens  capable of affecting  to many plant  species, such as tomato, potato, tobacco, peppe etc. In order to generate fransgenic tobacco plants resistant to both TMV and CMV, RNA interference  (RNAi) technology hasbeen applied in this study. A multi-fragment  of 625 bp - CPi (including  305 bp from  nucleotide  159 - 463 of TMV  cp gene  and  313 bp  from  nucleotide  315 -  627  of  CMV cp gene)  was used  to  construct  a  expression vector  containing T-CMV-CP  RNAi  in order to silence the CP gene of both TMV and CMV. This  construct was fransformed into tobacco plants (Nicotiana tabacum, cv. K326) via grobacterium tumefaciens.  The PCRT-PCR  and ELISA  analyses indicated that the CPi multi-fragment  was stably integrated  in tobacco genome and resulted in the absence of TMV and CMV in the inoculated transgenic lines. The resistant valuation of TO fransgenic tobacco  plants  after  three  times  challenge  with  TMV  and  CMV  revealed  that  34/48  (70.8%) fransgenic  lines were completely resistant to both studied vuuses.